Designing brutal multiplayer video games - Marshall, Joe; Linehan, Conor; Hazzard, Adrian (2016)
Non-digital forms of play that allow players to direct brute force directly upon each other, such as martial arts, boxing and full contact team sports,are very popular. However, inter-player brutality has largely been unexplored as a feature of digital gaming. In this paper, we describe the design and study of 2 multi-player games that encourage players to use brute force directly against other players. Balance of Poweris a tug-of-war style game implemented with Xbox Kinect, while Bundleis a playground-inspired chasing game implemented with smartphones. Two groups of five participants(n=10) played both games while being filmed, and were subsequently interviewed. A thematic analysis identified five keycomponents ofthe brutalmultiplayer video gameexperience, which informsa set of sevendesign considerations.This work aims to inspire the design of engaging game experiences based on awareness and enjoyment of our own and others’ physicality.